2015
DOI: 10.1182/blood-2014-12-619155
|View full text |Cite
|
Sign up to set email alerts
|

Lyn sustains oncogenic signaling in chronic lymphocytic leukemia by strengthening SET-mediated inhibition of PP2A

Abstract: Key Points• Cytosolic HSP90-bound Lyn mediates resistance to apoptosis by strengthening PP2A/SET interaction in CLL cells.• FTY720-analogues antagonizing the PP2A/SET interaction and Lyn inhibitors may provide a therapeutic approach of CLL.Aberrant protein kinase activities, and the consequent dramatic increase of Ser/Thr and -Tyr phosphorylation, promote the deregulation of the survival pathways in chronic lymphocytic leukemia (CLL), which is crucial to the pathogenesis and progression of the disease. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 56 publications
2
53
0
1
Order By: Relevance
“…Lyn, a gene target of WDR5, is a tyrosine kinase belonging to the Src family kinases (SFKs) and plays a crucial role in the onset and progression of CLL [3942]. It has been reported that the existence of a TK network composed of the tyrosine AXL, Lyn and SYK, promotes cell resistance to nilotinib treatment and drives Bcr–Abl-independent CML cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Lyn, a gene target of WDR5, is a tyrosine kinase belonging to the Src family kinases (SFKs) and plays a crucial role in the onset and progression of CLL [3942]. It has been reported that the existence of a TK network composed of the tyrosine AXL, Lyn and SYK, promotes cell resistance to nilotinib treatment and drives Bcr–Abl-independent CML cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of FTY720 allows it to act as a functional antagonist of the sphingosine-1-phosphate receptors (S1PRs), leading to sequestration of lymphocytes and immune suppression [29, 30]. Analogs of FTY720 that are incapable of being phosphorylated by sphingosine kinase-2 lack these immunosuppressive properties but retain their ability to activate PP2A and induce apoptosis [31-33], suggesting that the effect on PP2A is independent of S1PR related signaling.…”
Section: Pp2a Activationmentioning
confidence: 99%
“…An additional example of oncogene-induced PP2A inactivation was proposed in a model of chronic lymphocytic leukemia (CLL) [33]. The authors demonstrated increased phosphorylation of PP2A-C at Tyr307 in CLL cells but not normal B cells, and conclude that PP2A-C hyperphosphorylation is a result of LYN (a SRC family kinase) overexpression and leads to PP2A inhibition via increased association of PP2A-C with SET.…”
Section: Pp2a Activationmentioning
confidence: 99%
“…Antigen binding to the BCR induces clustering of BCR components at the cell membrane, along with phosphorylation of some components by activated Src family kinases (Lyn, Blk) e.g. [32]. We have previously shown that in T cells, tyrosine phosphorylation of Kv1.3 by the Src family kinase p56lck resulted in a decrease of its activity [33].…”
Section: Cell Physiolmentioning
confidence: 99%